Mesoscale imaging of the human cerebellum reveals converging regional specialization of its morphology, vasculature, and cytoarchitecture - Nikos Priovoulos; Pierre-Louis Bazin; Emma J. P. Brouwer; Jorge F. Mejías; Matthijs H. S. de Buck; Anneke Alkemade; Wietske van der Zwaag; Matthan W. A. Caan (Proceedings of the National Academy of Sciences, 2026)
The human cerebellar cortex, despite containing the majority of the brain’s neurons, remains poorly characterized in vivo due to its extreme folding and thin laminar architecture. Here, we present a high-resolution imaging framework based on parallel-transmit, motion-corrected, ultra-high-field (7T) MRI paired with an automated, anatomically faithful cerebellar segmentation pipeline. This enables detailed quantification of cerebellar morphology and vascular architecture at scales previously inaccessible in living humans, as validated with postmortem data. Applying this framework, we uncover consistent interlobular heterogeneity in both cortical thickness and vascularization. These spatial gradients relate to differences in the granular layer from 3D-histology data. Our findings suggest that the cerebellar granular layer may act as a structural determinant of vascular density, linking anatomical features with metabolic load. These findings align cerebellar structure–function relationships with similar findings in the neocortex, where morphology reflects functional specialization and energy consumption. Our results also suggest that the in vivo imaging biomarkers we derive may offer broad avenues to monitor cerebellar involvement in neurological diseases such as multiple sclerosis, where granular layer pathology is prominent. Our study provides both insights into cerebellar organization and a toolset for studying cerebellar contributions to cognition and pathology.